2020
DOI: 10.1177/0253717620935581
|View full text |Cite
|
Sign up to set email alerts
|

Statewide Survey of Psychological Distress Among People of Tamil Nadu in the COVID-19 Pandemic

Abstract: Background: COVID-19-driven pandemic has caused panic, fear, and stress among all strata of society. The study aimed to assess stress and the factors that influence it in a representative population in the state of Tamil Nadu (TN)—a state in the southern India where the levels of stress have not been measured yet. Methods: From April 13 to April 25, 2020, we conducted an online survey among the TN population using the snowball sampling technique, collecting basic demographic data. CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
6
23
1
1
Order By: Relevance
“…The survey script was available for all devices. The questionnaire used (Additional Table 1) was similar to those used in China during the tumultuous time of the COVID-19 epidemic [11], and to small surveys in Saudi Arabia [14], India [15], Iran [16], Brazil [17], Nepal [18], and Germany [19]. The socio-demographic section was modified to be more compliant with the Italian situation.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The survey script was available for all devices. The questionnaire used (Additional Table 1) was similar to those used in China during the tumultuous time of the COVID-19 epidemic [11], and to small surveys in Saudi Arabia [14], India [15], Iran [16], Brazil [17], Nepal [18], and Germany [19]. The socio-demographic section was modified to be more compliant with the Italian situation.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…A study done in April 2020 at Tamil Nadu through online mode had similar results of younger age people having more psychological stress than older people. 13 The young and middle age had higher scores of distress in a study done in Australia using DASS21 during the start of the pandemic. 14 The Normative aging study (NAS) explains the possible reasons for this observation.…”
Section: Discussionmentioning
confidence: 95%
“…A similar study conducted in Tamil Nadu reported that 23% of respondents were more stressed than usual due to COVID-19, and 8.01% avoided news coverage because this worsened their stress. 9 …”
Section: Suicide and Mental Health In The Context Of Covid-19 In Indimentioning
confidence: 99%